The Influence of Convenience, Pricing, Accessibility, and Product Variety on the Perceived Practical Utility of Online Shopping - Rhitchelle Therese Egera; Lovelyn C. Trazona; Ramie Lou B. Abordonado; Mike Kevin C. Caballero; Marilou C. Obejero; Easter Mae C. Rita; Lalaine O. Narsico; Peter G. Narsico (International Journal of Multidisciplinary: Applied Business and Education Research, 2026)
Today, online shopping has become a core activity of consumers, especially among digital-savvy college students. While the importance of convenience, price, easy access and product variety is well known, the combined effect of these four factors on perceived practical utility has not been investigated. Among 380 college students in Cebu City, Philippines, the relationships established between these four features and practical utility have been examined using this descriptive-correlational quantitative design. Information was gathered using a structured questionnaire (14 items; Cronbach’s α = 0.897) and analysed using descriptive statistics and a regression model. Participants believed that online shopping is convenient (M = 3.98), provides price advantages (M = 4.04), high accessible (M = 4.30) and provides various product options (M = 4.09). The results indicated that convenience had a significant positive effect on practical utility (β = 0.66, p < .001), price (β = 0.61, p < .001), accessibility (β = 0.74, p < .001) and product variety (β = 0.73, p < .001). However, this was not the case in multiple regression model (R² = .58) where accessibility (β = 0.34), convenience (β = 0.28) and product variety (β = 0.24) remained significant while price advantage became non-significant (p = .137). The practical utility of online shopping is provided by accessibility, convenience and assortment of products. Price is less important in combination with other factors.